Access and reproductive health rights for women in West Papua, is it affordable? - Yustina Tyas Kurniawati (BKM Public Health and Community Medicine, 2021)
According to the Indonesian Health Profile 2017 shows that the Maternal Mortality Rate (MMR) shows 305 per 100,000 live births. The coverage of health services K4 for pregnant women explains that West Papua has a percentage of 23.19% in 2017. This percentage is the smallest figure compared to other provinces1. Meanwhile, deliveries percentage at health facilities are still below the national average, which is only 55%. This below average percentage includes births attended by skilled birth attendants and family planning needs that have been met with modern contraceptive methods. In addition, only 56% of adult women and adolescents aged 15–49 years had family planning needs met with modern contraceptive methods in 2015, and one in four births without assistance from a skilled birth attendant. Lower levels of access for mothers and children in rural areas2. There are still many people in West Papua who live with a deficient economy. The Mother and Child program in West Papua should have run well, but it was hampered and not implemented for years (one of which was in the Puskesmas Mare District, Suswa). In addition, the lack of equality in the development of existing health service facilities makes access to quality health unequal. The hospital in Sorong has more resources than the village clinics. Access to health insurance and ASKES is also not as good as in Java, which should be obtained easily and quickly, but in West Papua it takes a long time to get a community health insurance (Jamkesmas) or health insurances (ASKES) card, even up to two years3. People who are non-Papuans but live in West Papua have easier access to health care than indigenous Papuans. This results in inequality and results in differences in socio-economic status in Papua where Papuans have been affected by this system. The transmigrants who have adequate education and skills dominate market economic growth and ignore Papuans, which makes Papuans feel the benefits and impacts on the economy sectors4. Several districts in West Papua are not yet have a hospital due to difficulties in acquiring land or customary rights for the establishment of hospitals5. These conditions make many indigenous Papuan mothers still do not know the importance of their health needs, especially their reproductive health. They surrender to the existing circumstances and limitations. To reduce and overcome this, any several things that can be done.